Interference fringe suppression in tunable diode laser absorption spectroscopy based on CEEMDAN-WTD - Wang, Shoulin; Gong, Weihua; Wang, Zhaowei; Wei, Yubin; Li, Yanfang; Zhang, Tingting; Zhang, Qinduan; Zhang, Lin; Song, Fugang; Zhang, Wei; Liu, Tongyu (Frontiers in Physics, 2022)
Due to the interference fringes in multi-reflective gas cell, the detection sensitivity of system will significantly decrease in tunable diode laser absorption spectroscopy (TDLAS). In this work, the algorithm of Complete Ensemble Empirical Mode Decomposition with Adaptive Noise (CEEMDAN) combined with a Wavelet Threshold Denoising (WTD) was proposed. The effective of the algorithm was verified by simulation analysis and constructing a CO2 detection system based on TDLAS. After CEEMDAN-WTD processing, the noisy intrinsic mode function (IMF) component, the pure IMF components and residual component of detection signal were identified and reconstructed successfully. As a result of simulation analysis, the signal-to-noise ratio (SNR) was improved by 1.87 times and the root mean square error (RMSE) was reduced by 37.6% compared with the moving average algorithm. For CO2 detection system, R2 = 0.999 was calculated in the calibration experiment. And, using Allan variance analysis, the stability and limit of detection (LOD) was estimated to be 7.82 ppm at an average time of 1s, and 3.08 ppm at an averaging time of 148 s. The demonstrated results sufficiently validated that CEEMDAN-WTD algorithm can effectively suppress interference fringes noise in TDLAS.